Pengaruh Kompetensi Guru Bimbingan Konseling Terhadap Pelaksanaan Bimbingan Kelompok Siswa Kelas XI SMA Negeri 3 Tondano - Filen F.G Rondonuwu; Meisie L. Mangantes (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study uses a quantitative approach with correlational research methods. Correlational research is a study to determine the relationship or influence between the variables studied. The sample in the study was 40 students of class XI SMA Negeri 3 Tondano. Data collection techniques in this study used an understanding questionnaire, further study, interviews, and documentation as supporting techniques. Based on the results of the study, it is known that there is an influence on the competence of counseling teachers in carrying out group guidance at SMA Negeri 3 Tondano. Based on the research data and the results of the analysis carried out, it was found that the significance value was 0.000 <0.05, indicating that the counseling guidance teacher competence variable (X) had an effect on the group guidance implementation variable at SMA Negeri 3 Tondano (Y) while based on the results of the test- t obtained t value of 8.205 > t table 2.058. Based on the results of this analysis, it can be concluded that there is an influence of the counseling teacher's competence on the implementation of group counseling at SMA Negeri 3 Tondano.